2016
DOI: 10.1002/jcla.21938
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Apoptotic Lymphocytes Through Sysmex XN‐1000 As a Diagnostic Marker for Mononucleosis Syndrome

Abstract: On Sysmex XN-1000, dot-plot observation allowed immediate detection of IM. Meanwhile, an algorithm based on the parameters on these plots can be calculated with excellent performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(26 reference statements)
0
9
0
1
Order By: Relevance
“…In a recent paper, Sale observed that in patients with MNS, the SSC‐SFL dot plot supplied by Sysmex XN‐10 included a population of presumed apoptotic lymphocytes. Using a particular gating strategy, they counted the percentage of events of the population of apoptotic lymphocytes (Ly‐Apopt).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper, Sale observed that in patients with MNS, the SSC‐SFL dot plot supplied by Sysmex XN‐10 included a population of presumed apoptotic lymphocytes. Using a particular gating strategy, they counted the percentage of events of the population of apoptotic lymphocytes (Ly‐Apopt).…”
Section: Discussionmentioning
confidence: 99%
“…The haematology analysers can measure some positional parameters of the different cell populations in PB that can be useful in the identification of some pathologies, such as granulocytic dysplasia or sepsis . Furthermore, some papers suggest that lymphocyte positional parameters can be useful to differentiate viral diseases (VD) from lymphoproliferative disorders, as well as to detect the presence of Sézary cells or mantle cell lymphoma cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cell types were lost mostly by DGCun, possibly due to mechanical and chemical destruction. Differences of cell proportions after DGC compared to the respective smear could result from cell apoptosis during DGC since—unlike in a common hemocytometer analysis by light scatter and peroxidase activity—apoptotic cells can easily be excluded during differential smear analysis [29]. RBCL effects on cell concentrations, however, are more difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…The reference for the Sysmex XN‐Series is the XN‐1000 as a high throughput automated hematology analyzer and was first evaluated in 2012 for both whole blood mode and body fluid mode 4‐6 . Thereafter, its accuracy and precision have been described for various sample types and medical conditions and compared with other leading hematology analyzers 6‐10 . A subset of the XN technology and measurement channels are also used in XN‐L series: A complete blood count (CBC) with a 6‐part white blood cell (WBC) differential, where immature granulocytes (IG) are counted in addition to the 5‐part differential.…”
Section: Introductionmentioning
confidence: 99%